Composite fabrication for improvement of thermoelectric properties in AlSb. (May 2020) - Shawon, A.K.M. Ashiquzzaman; Kim, Il-Ho; Ur, Soon-Chul
Abstract: The III-V semiconductor AlSb has an indirect band gap and a relatively moderate thermal conductivity. Intrinsic AlSb has a promising thermopower, but a very high resistivity and the lattice thermal conductivity keeps the ZT value significantly low. This work shows a process of reducing the thermal conductivity by formation of binary composite with Zn4 Sb3 . β-Zn4 Sb3 powders were synthesized by sintering of cold compacted pellets and AlSb was fabricated using controlled casting in tapped graphite crucible. Inclusion and dispersion of 10 wt % β-Zn4 Sb3 within the matrix of AlSb has reduced the thermal conductivity by more than 5 times. In addition, the composite shows improved electrical conductivity without a significant decrease in thermopower. Overall, the thermoelectric figure of merit shows proportionality with the increasing amount of β-Zn4 Sb3, where the ZT increases significantly.